Training direct-care staff to implement an iPad®-based communication intervention with adults with developmental disability. (2nd October 2017) - van der Meer, Larah; Waddington, Hannah; Sigafoos, Jeff; Balandin, Susan; Bravo, Alicia; Ogilvie, Emily; Matthews, Tamyra; Sawchak, Anastasia
Abstract : Objectives: To evaluate the effects of a program for training direct-care staff to implement an iPad®-based communication intervention with adults with developmental disability and severe communication impairment. Methods: Participants were 11 adults with developmental disability and 19 direct-care staff drawn from two day program settings. Direct-care staff completed training on how to implement the iPad®-based intervention. Staff were trained using PowerPoint® and video presentations, role play, practice, and feedback. A nonconcurrent multiple-baseline across settings design was used to evaluate the effects of the training program on fidelity of implementation by direct-care staff and the frequency of functional communicative acts by the adults with developmental disability. Eleven direct-care staff (five from Setting 1 and six from Setting 2) also completed a social validity questionnaire on the acceptability and usefulness of the training program. Results: After the training program, fidelity of implementation and frequency of functional communication increased. These gains were maintained at the follow-up in Setting 1, but not in Setting 2. Direct-care staff in both settings rated the training program as acceptable and useful. Conclusion: Direct-care staff learned to implement an iPad®-based communication intervention to increase functional communication in adults with developmental disability and severe communication impairment. The training program showed promise, but additional research is needed to validate its effectiveness.